Physiological and biometric evaluations of lettuce grown in an aquaponic system under different conditions (Research, Society and Development, 2023)
Producing food in a practical, sustainable and inclusive way are some of the advantages that the aquaponic system, which provides, however, studies on productive performance in the Brazilian Midwest are scarce. Thus, the present study aimed to analyze the physiological and nutritional characteristics of lettuce grown in aquaponics. For this, an experiment was carried out in the units of the Department of Irrigation and Drainage of IF Goiano, Rio Verde/Goiás Campus, consisting of reservoir (1 m3), decanter, biological filter, pump and aerator, in addition to six hydroponic gutters in each experimental unit, which housed 11 plants/trough. The experimental design was completely randomized, in a factorial arrangement with three fish populations (PP30=30, PP60=60 and PP90=90 fish w/m³) and two volumes of filter material (VF40=40 and VF60=60), for the first cycle and (VF50=50 and VF70=70 liters of expanded clay), for the second cycle, with three replications. Physiological analyses and biometric variables were analyzed at 45 after sowing. The data obtained were submitted to variance analysis and, when necessary, the means were compared by the Tukey Test, using the SISVAR® computer program. Due to what was analyzed, we can say that the highest values achieved for physiological parameters were for a volume of filter material of 70 L. In relation to the fish population, we observed that a population of 30 fish, presented satisfactory results. Biometric parameters, the highest means were achieved with a lower volume of filter material for a population of 30 fish. For macronutrients, the highest values were achieved with a higher volume of filter material for a population of 30 fish. For micronutrients, it was observed that a population of 30 fish is sufficient to ensure a good development of lettuces, with a biofilter with a minimum capacity of 50 liters. Significant variations in macro and micronutrients were observed, supposedly because they were discarded along with excess residues taken from decanters or because they suffered precipitation due to high pH values. The use of a biofilter with greater capacity is important to maintain adequate water quality levels, whether by reducing pH or ammonia.